Socru: typing of genome-level order and orientation around ribosomal operons in bacteria. Issue 7 (25th July 2020) - Page, Andrew J.; Ainsworth, Emma V.; Langridge, Gemma C.
Abstract : Rearrangements of large genome fragments occur in bacteria between repeat sequences and can impact on growth and gene expression. Homologous recombination resulting in inversion between indirect repeats and excision/translocation between direct repeats enables these structural changes. One form of rearrangement occurs around ribosomal operons, found in multiple copies across many bacteria, but identification of these rearrangements by sequencing requires reads of several thousand bases to span the ribosomal operons. With long-read sequencing aiding the routine generation of complete bacterial assemblies, we have developed socru, a typing method for the order and orientation of genome fragments between ribosomal operons. It allows for a single identifier to convey the order and orientation of genome-level structure and we have successfully applied this typing to 433 of the most common bacterial species. In a focused analysis, we observed the presence of multiple structural genotypes in nine bacterial pathogens, underscoring the importance of routinely assessing this form of variation alongside traditional single-nucleotide polymorphism (SNP) typing.